Empowerment of Rural Women through Education and Economic Support: An Overview - Agarwal, Dr. Rajesh Kumar (Innovative Research Thoughts, 2017)
Small businesses, also known as micro, small, and medium enterprises (MSMEs), are an essential part of India's economy, coming in second only to agriculture. However, the government's actions may either damage or assist such 'business culture.' Small company law has been enacted in numerous nations, including the United States, Canada, and Australia. The MSME sector has a critical role to play in achieving India's goal of becoming a 5 trillion economy. As a result, India's MSME strategy is now focused on engaging with MSMEs during their full lifecycle in order to ensure that this sector is healthy, robust, and competitive. From the present 29 percent, this programme aims to raise the percentage of MSMEs in the country's GDP to 50 percent.